Bentuk Penanggulangan dan Pencegahan terhadap Tindak Pidana Penipuan Lowongan Kerja Online - Alifia Risma Marselyna; Indrawati Indrawati; Nahdiya Sabrina (University of Merdeka Malang, 2020)
Currently, there are many crimes that take advantage of the sophistication of internet developments, such as crimes that are committed online or commonly called Cyber Crime. This is based on the argument that Cyber Crime is an activity that uses computers as a medium that is supported by a communication system, whether it’s a Dial Up System, using a telephone line, or a wireless system that uses a special wireless antenna. One form of crime related to the misuse of information technology facilities is a crime or criminal act of online job vacancies as regulated in Article 378 Book II of the Criminal Code (KUHP) and Article 28 paragraph (1) Jo. Article 45 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transaction. This study seeks to answer the background of fraud in online job vacancies as well as a form of countermeasures against fraud in online job vacancies. This study uses a normative juridical research method.